Emerging Concepts in Pathogenesis, Multiomics Applications, and Clinical Research in Lymphangioleiomyomatosis - Yu, Jane J.; Gupta, Nishant; Guo, Minzhe; Olatoke, Tasnim; Xu, Yan (Seminars in Respiratory and Critical Care Medicine, 2025)
Lymphangioleiomyomatosis (LAM) is a rare, female-predominant, low-grade neoplasm characterized by infiltration of abnormal smooth muscle-like and epithelioid cells into the lung parenchyma, leading to cystic changes and progressive respiratory failure. In recent years, LAM has been an exemplar of meaningful progress in a rare lung disease, driven by close collaboration between patients, scientists, and clinicians, leading to the development of the U.S. Food and Drug Administration (FDA)-approved therapy, a diagnostic biomarker, a worldwide clinic network, and clinical practice guidelines. Integrating state-of-the-art bioinformatics and experimental approaches is helping accelerate the scientific progress in LAM and promises the development of novel biomarkers and therapies in the coming few years.
Keywords: lymphangioleiomyomatosis; diagnostic biomarker; progressive respiratory failure; bioinformatics applications in LAM